Electrochemical oxidation of methanol on Pt nanoparticles dispersed on RuO2 - Villullas, H. M.; Mattos-Costa, F. I.; Bulhoes, LOS (Amer Chemical Soc, 2004)
Pt-modified RuO2 was prepared by a sol-gel procedure on titanium substrates in the form of thin films of similar to2-mum thickness. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analyses showed that these films actually consist of Pt nanoparticles dispersed in RuO2 and that neither metallic Ru nor Pt-Ru alloy are present on the surface. Electrodes with different Pt:Ru nominal compositions were prepared and their electrocatalytic activity for the oxidation of methanol was investigated by potential sweeps and chronoamperometry. The results obtained show an enhancement effect for methanol oxidation that can be interpreted as associated to the formation of hydrous oxides on the RuO2 surface.